The Effects of Platelet-Derived Growth Factor-BB on Human Dental Pulp Stem Cells Mediated Dentin-Pulp Complex Regeneration. (24th October 2017) - Zhang, Maolin; Jiang, Fei; Zhang, Xiaochen; Wang, Shaoyi; Jin, Yuqin; Zhang, Wenjie; Jiang, Xinquan
Abstract: Dentin-pulp complex regeneration is a promising alternative treatment for the irreversible pulpitis caused by tooth trauma or dental caries. This process mainly relies on the recruitment of endogenous or the transplanted dental pulp stem cells (DPSCs) to guide dentin-pulp tissue formation. Platelet-derived growth factor (PDGF), a well-known potent mitogenic, angiogenic, and chemoattractive agent, has been widely used in tissue regeneration. However, the mechanisms underlying the therapeutic effects of PDGF on dentin-pulp complex regeneration are still unclear. In this study, we tested the effect of PDGF-BB on dentin-pulp tissue regeneration by establishing PDGF-BB gene-modified human dental pulp stem cells (hDPSCs) using a lentivirus. Our results showed that PDGF-BB can significantly enhance hDPSC proliferation and odontoblastic differentiation. Furthermore, PDGF-BB and vascular endothelial growth factor (VEGF) secreted by hDPSCs enhanced angiogenesis. The chemoattractive effect of PDGF-BB on hDPSCs was also confirmed using a Transwell chemotactic migration model. We further determined that PDGF-BB facilitates hDPSCs migration via the activation of the phosphatidylinositol 3 kinase (PI3K)/Akt signaling pathway. In vivo, CM-DiI-labeled hDPSCs were injected subcutaneously into mice, and our results showed that more labeled cells were recruited to the sites implanted with calcium phosphate cement scaffolds containing PDGF-BB gene-modified hDPSCs. Finally, the tissue-engineered complexes were implanted subcutaneously in mice for 12 weeks, the Lenti-PDGF group generated more dentin-like mineralized tissue which showed positive staining for the DSPP protein, similar to tooth dentin tissue, and was surrounded by highly vascularized dental pulp-like connective tissue. Taken together, our data demonstrated that the PDGF-BB possesses a powerful function in prompting stem cell-based dentin-pulp tissue regeneration. Abstract : Platelet-derived growth factor-BB through enhancing human dental pulp stem cells (hDPSC) proliferation, odontogenic differentiation, angiogenesis, and also facilitating stem cell homing to promote hDPSC-mediated dentin-pulp complex regeneration.